Pulmonary edema and acute respiratory distress syndrome in a child with Plasmodium falciparum malaria - Tebruegge, Marc; Pantazidou, Anastasia (Journal of Pediatric Infectious Diseases, 2007)
We report the case of a 12-year-old girl who had returned to the UK from Nigeria two days prior to presenting with fever and breathing difficulties. She had high-grade pyrexia, was mildly dehydrated and lethargic but there were no abnormal findings on auscultation. Initially she required 5l/min of oxygen to maintain adequate oxygenation. The chest X-ray showed bilateral shadowing consistent with pulmonary edema and early acute respiratory distress syndrome (ARDS). The patient was admitted to pediatric intensive care unit and intubated six hours later due to increasing oxygen requirement and deteriorating level of consciousness. Thin blood films revealed Plasmodium falciparum infection with high-grade parasitemia (13%). The girl was commenced on intravenous quinine. No further complications were observed, apart from mild renal impairment. She made a remarkable recovery, was extubated after four days of ventilation and discharged without residual problems five days later. Lung function tests at follow up revealed no abnormalities. Acute lung injury (ALI) secondary to P. falciparum malaria, which includes pulmonary edema and ARDS at the severe end of the spectrum, is not uncommon in adults, and has been reported to occur in up to 30% of malaria patients who require admission to the intensive care unit. In contrast, ALI is a relatively rare complication in pediatric patients. Many of these patients with ALI simultaneously develop other complications of malaria including acute renal failure, hypotension and cerebral malaria. Adult studies have reported overall mortality rates of approximately 50% in patients with ALI secondary to malaria; however, the majority of survivors have no long-term respiratory sequelae.
Keywords: Malaria; child; P. falciparum; acute lung injury; ARDS; pulmonary edema